2007
DOI: 10.1002/hipo.20298
|View full text |Cite
|
Sign up to set email alerts
|

A navigational guidance system in the human brain

Abstract: Finding your way in large-scale space requires knowing where you currently are and how to get to your goal destination. While much is understood about the neural basis of one's current position during navigation, surprisingly little is known about how the human brain guides navigation to goals. Computational accounts argue that specific brain regions support navigational guidance by coding the proximity and direction to the goal, but empirical evidence for such mechanisms is lacking. Here, we scanned subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
150
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(177 citation statements)
references
References 44 publications
22
150
1
1
Order By: Relevance
“…Behavioral studies in humans support the proposition that navigation is based on heading vectors rather than step-by-step movement along a path of identifiable locations (Wang and Spelke, 2002;Waller and Haun, 2003;Muehl and Sholl, 2004;Spiers and Maguire, 2007). For example, Bailenson et al (2000) found that, given a choice between equal-distance routes between two points, subjects reliably chose the route whose initial segment direction was closer to the global vector to the goal.…”
Section: Human Navigationmentioning
confidence: 85%
“…Behavioral studies in humans support the proposition that navigation is based on heading vectors rather than step-by-step movement along a path of identifiable locations (Wang and Spelke, 2002;Waller and Haun, 2003;Muehl and Sholl, 2004;Spiers and Maguire, 2007). For example, Bailenson et al (2000) found that, given a choice between equal-distance routes between two points, subjects reliably chose the route whose initial segment direction was closer to the global vector to the goal.…”
Section: Human Navigationmentioning
confidence: 85%
“…As we have seen in the previous section, the generation of an allocentric (world-centered) representation of locations -a cognitive map -is a key process in spatial navigation. However, while knowledge of spatial environment is clearly crucial, the primary purpose of navigation is to reach specific locations or goals (a final destination or intermediate landmarks) that are the raison d'être of navigation (Spiers & Maguire, 2007). From this point of view, spatial navigation may be described as a specific case of a more general goal-oriented behavior.…”
Section: Goal Planning In Spatial Navigation and Discourse Processesmentioning
confidence: 99%
“…Both regions are activated by way-finding compared with processing static scenes (Maguire et al, 1998) or route-following (Hartley et al, 2003). The PPC has also been associated with spatial planning (Spiers and Maguire, 2006) and activity there correlates with egocentric distance to the goal (Spiers and Maguire, 2007). Animal studies reveal neurons in medial parietal areas that respond to the position of stimuli in allocentric space (Galletti et al, 1993;Dean and Platt, 2006), whereas neurons in the more lateral intraparietal sulcus respond to combinations of egocentric and allocentric locations (Andersen et al, 1985;Snyder et al, 1998) and to the animal's position along a trajectory (Nitz, 2006).…”
Section: Detour Planningmentioning
confidence: 99%